IMPLEMENTASI KULIAH KERJA MANAJEMEN BISNIS SYARIAH (KKMBS) DI LEMBAGA PENELITIAN DAN PUBLIKASI ILMIAH (LPPI) MEDAN - Mr. Irfan Chema; Cita Ayni Putri Silalahi (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Higher education based on Islamic knowledge requires graduates who not only master Islamic management theory but also possess practical skills and professionalism. The Islamic Business Management Work Lecture (KKMBS) program provides practical learning that integrates managerial competencies, Islamic business ethics, and students’ soft skills. This study aims to describe the implementation of KKMBS at the Institute of Research and Scientific Publication (LPPI), Universitas Muslim Nusantara (Al-Washliyah) Medan, including student activities, competency achievements, challenges, and institutional guidance. A qualitative approach was used with data collection through observation, informal interviews, and documentation. Data analysis employed Miles and Huberman’s interactive model. Results show students gained hands-on experience in research administration, scientific publication, teamwork, and the application of Islamic ethical values such as trustworthiness and responsibility. Intensive guidance helped students overcome adaptation challenges. In conclusion, KKMBS strengthens students’ technical, social, and ethical competencies and prepares them for professional work in accordance with Islamic Business Management principles